Analisis Return on Assets (ROA) dalam menilai kinerja keuangan Bank BCA Syariah periode 2020–2024 - alhadid, chealshe oliviana fega; Aisyah, Esy Nur (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the profitability level of Bank BCA Syariah using the Return on Assets (ROA) ratio as the primary indicator of financial performance for the period 2020–2024. ROA is employed to assess the bank’s ability to generate profit based on the total assets it manages. The research utilizes secondary data obtained from the annual financial statements of BCA Syariah and applies a descriptive quantitative approach by observing the year-to-year trend of ROA. The findings indicate that the ROA of BCA Syariah remained relatively stable at the beginning of the period and showed a noticeable improvement in the following years, particularly in 2022–2023. This upward trend reflects enhanced asset management efficiency and improved operational effectiveness. Although complete financial data for 2024 is not yet fully available, preliminary indications suggest that the bank continues to maintain healthy profitability. Overall, the development of ROA during the study period demonstrates that BCA Syariah is in solid financial condition and capable of optimizing its assets to generate consistent profit.